2016
DOI: 10.1161/circulationaha.116.023831
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Versus Compression-Only Versus No-Bystander Cardiopulmonary Resuscitation for Pediatric Out-of-Hospital Cardiac Arrest

Abstract: In this population-based study of pediatric OHCA in Japan, both conventional and compression-only CPR were associated with superior outcomes compared with no-bystander CPR. Unadjusted outcomes with conventional CPR were superior to compression-only CPR, with the magnitude of difference attenuated and no longer statistically significant after statistical adjustments. These findings support randomized clinical trials comparing conventional versus compression-only CPR in children, with conventional CPR preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 40 publications
0
35
2
2
Order By: Relevance
“…Both studies showed better neurological outcomes (risk difference −3.30, 95% CI −4.88, −1.71), and survival (risk difference −7.04, 95% CI −9.58, −4.50) in children who received bystander CPR with compressions and ventilations compared with compression-only CPR. Since publication of the systematic review, two further studies have been published [52,53] which were also reviewed by the ILCOR Paediatric Task Force when considering the 2017 CoSTR. These studies were consistent with previous studies in showing that receiving any form of CPR was better than no CPR.…”
Section: Ilcor Costr In Context Of Erc Guidelinesmentioning
confidence: 99%
“…Both studies showed better neurological outcomes (risk difference −3.30, 95% CI −4.88, −1.71), and survival (risk difference −7.04, 95% CI −9.58, −4.50) in children who received bystander CPR with compressions and ventilations compared with compression-only CPR. Since publication of the systematic review, two further studies have been published [52,53] which were also reviewed by the ILCOR Paediatric Task Force when considering the 2017 CoSTR. These studies were consistent with previous studies in showing that receiving any form of CPR was better than no CPR.…”
Section: Ilcor Costr In Context Of Erc Guidelinesmentioning
confidence: 99%
“…The authors directly compared bystander chest compression-only CPR and CPR using chest compressions with rescue breaths in children >1 year of age who had cardiac arrest, including traumatic arrest, during 2011 and 2012. 8 A national dispatch-assisted instruction protocol was in use, and CPR guidelines recommended a compressionto-ventilation ratio of 30:2. Chest compression-only CPR and CPR using chest compressions with rescue breaths were associated with improved survival at 1 month and favorable neurological survival at 1 month compared with no bystander CPR.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…A number of register-based observational cohort studies have been carried out to compare CO-CPR with S-CPR, many of which have shown neutral results. [141][142][143] Differences in favour of S-CPR have been found in connection with paediatric arrests, 144 individuals younger than 18 years, 145 , and when EMS response-time were longer than 15 minutes. 146 Others have found higher survival for CO-CPR among patients found in VT/VF or treated with public AED.…”
Section: Compression-only Cprmentioning
confidence: 99%